Thermo-mechanical effect on the anisotropic permeability of a mudstone. (January 2023) - Yu, Hongdan; Lu, Chen; Chen, Weizhong; Yang, Diansen; Li, Honghui
Abstract: Tamusu mudstone is a candidate geological medium for high-level radioactive waste disposal in China. This paper investigates its anisotropic hydraulic properties. Permeability measurements were conducted on two kinds of samples, i.e., along the directions perpendicular and parallel to the beddings, under different stress conditions with heating-cooling cycles (20 → 40→60 → 80→60 → 40→20 °C). The results confirmed the hydraulic anisotropy of Tamusu mudstone. Increasing lithostatic pressure decreases the intrinsic permeability k and hydraulic conductivity K and decreases the hydraulic anisotropy of Tamusu mudstone. The temperature significantly affects the hydraulic properties: the k values exhibit a negative correlation with temperature. A notable variation in parallel hydraulic properties upon temperature elevation indicates that the thermal effect is more crucial in the direction parallel at low lithostatic pressure. A notable effect of thermal paths on the hydraulic properties of Tamusu mudstone was exhibited through the different K or k at the same temperatures before and after heating-cooling cycles.